G95(P) Sudden infant death syndrome and car seats: a systematic literature review. (12th March 2018) - Plumptre, I; Phillips, C; Williams, S; Plumptre, C
Abstract : Aims: Sudden infant death syndrome (SIDS) was responsible for 191 infant deaths in England and Wales in 2015. 1 SIDS rates have declined substantially in recent years, thanks to successful campaigns about known modifiable risk factors such as smoking in pregnancy and sleeping positions. 2 Guidance about at-home sleeping to reduce SIDS (such as avoidance of co-sleeping, bedding and temperature) is widely available. However, guidance about safe out-of-home sleeping, for example in buggies or car seats, is more limited. We aimed to assess the evidence about the role of car seats in SIDS. Methods: We conducted a systematic literature review in PubMed using the search terms 'sudden infant death syndrome AND car seat' or 'SIDS AND car seat'. Article abstracts were screened for relevance. Articles discussing infant death in a car seat from an explained cause were excluded. Results: A systematic literature review revealed 10 results. Of these, abstract screening excluded 7 results for describing booster seats (n=2), and explained deaths such as injury or hanging (n=5). Of included articles, one retrospective review of 11 717 infant deaths identified that out-of-home SIDS were 2.6 times more likely to be associated with a carseat or stroller. 3 A second retrospective review highlighted 14 car seat associated unexplained infant deaths out of 1465 autopsies, 10 of which were outside of travel use. 4 This supports recommendations that car seats should be used for travel only. 5 3 further articles identified from references highlighted work demonstrating reduced oxygen saturations in infants in simulated moving car seats. 6 This supports a separate finding that attributed 48% of car seat associated deaths to positional asphyxia. 7 Longer periods in car seats also increase the risk of airway obstruction. 8 Conclusions: Although car seats are an important legal requirement, 9 evidence suggests that prolonged periods in a car seat are dangerous for infants. However, there is a very limited evidence base for guidelines on exactly how long car seats should be used in infants. There is an urgent need for further research into the interplay of car seats and SIDS in order to produce practical advice for parents. References: . Office of National Statistics. Unexplained deaths in infancy: England and Wales, 2010 2015August;1–13. . The Lullaby Trust. Safer sleep advice . https://www.lullabytrust.org.uk/safer-sleep-advice/ . Kassa H, Moon RY, Colvin JD. Risk factors for sleep-related infant deaths in in-home and out-of-home settings. Paediatrics 2016;138(5):e20161124–e20161124. doi:10.1542/peds.2016-1124 . Bamber AR, Pryce J, Ashworth MT, Sebire NJ. Sudden unexpected infant deaths associated with car seats. Forensic Sci Med Pathol2014;10(2):187–192. doi:10.1007/s12024-013-9524-5 . Committee on Injuryand Poison Prevention and Committee on Fetus and Newborn. Safe Transportation of Premature and Low Birth Weight Infants. Pediatr1996;97(5):758–760. . Arya R, Williams G, Kilonback A, et al. Is the infant car seat challenge useful? A pilot study in a simulated moving vehicle. Arch Dis Child: Fetal Neonatal Ed2017;102(2):F136–F141. doi:10.1136/archdischild-2016-310730 . Batra EK, Midgett JD, Moon RY. Hazards associated with sitting and carrying devices for children two years and younger. J Pediatr2015;167(1):183–187. doi:10.1016/j.jpeds.2015.03.044 . Cote A, Bairam A, Deschenes M, Hatzakis G. Sudden infant deaths in sitting devices. Arch Dis Child2008;93(5):384–389. doi:10.1136/adc.2007.119180 9. Child car seats: the law . https://www.gov.uk/child-car-seats-the-rules